2019
DOI: 10.3390/antibiotics8020083
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of the Disparate: Co-ordinate Regulation in Antibiotic Biosynthesis

Abstract: Discovering new antibiotics is vital to combat the growing threat of antimicrobial resistance. Most currently used antibiotics originate from the natural products of actinomycete bacteria, particularly Streptomyces species, that were discovered over 60 years ago. However, genome sequencing has revealed that most antibiotic-producing microorganisms encode many more natural products than previously thought. Biosynthesis of these natural products is tightly regulated by global and cluster situated regulators (CSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 94 publications
2
25
0
Order By: Relevance
“…Even with a few different test systems used, the compounds cannot be detected if the appropriate PKS and NRPS are not expressed and the compounds are not produced. Production of polyketides and non-ribosomal peptides starts from the transcription of the respective biosynthesis genes (McLean et al, 2019). Therefore, we carried out the transcriptional analysis in order to find if the identified genes are expressed at all, and, if yes, to see if the expression is affected by the amount of the nutrients in the culture medium and/or by the culture growth phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with a few different test systems used, the compounds cannot be detected if the appropriate PKS and NRPS are not expressed and the compounds are not produced. Production of polyketides and non-ribosomal peptides starts from the transcription of the respective biosynthesis genes (McLean et al, 2019). Therefore, we carried out the transcriptional analysis in order to find if the identified genes are expressed at all, and, if yes, to see if the expression is affected by the amount of the nutrients in the culture medium and/or by the culture growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…Amos et al (2017) previously reported that in most cases transcription is a good indicator of the compound production. Expression of PKS and NRPS genes is regulated by the complex network of regulators acting as either activators or repressors at the transcription level (van der Heul et al, 2018; Wei et al, 2018; McLean et al, 2019). Despite extensive studies on the global regulator BldA, the only tRNA necessary for the translation of the UUA codons (Hou et al, 2018; van der Heul et al, 2018), little is known about regulation at the pre- and post-transcriptional levels, overall (Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…formation of the secondary multinucleated mycelium, sporulation) that occurs late in the growth phase. These metabolic and morphological changes are controlled by highly interconnected regulatory mechanisms that have been studied mostly at the transcriptional, translational and post-translational levels [4][5][6][7] . However, a clear link between global chromosome organization and metabolic differentiation has yet to be established.…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…For example, the production of actinorhodin in Streptomyces coelicolor is regulated by ActII-4 [19] and CprB [20]. There are also an increasing number of examples of coordinate regulation from one cluster-situated regulator on another BGC [21], such as with FscRI regulating both candicidin and antimycin production in Streptomyces albidoflavus S4 [22]. Lsr2 is a global transcriptional regulator conserved throughout the phylum Actinobacteria that plays an important role in the repression of gene expression.…”
Section: Introductionmentioning
confidence: 99%